Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2014
DOI: 10.1080/10643389.2013.829767
|View full text |Cite
|
Sign up to set email alerts
|

Fate and Bioavailability of Engineered Nanoparticles in Soils: A Review

Abstract: Interactions within natural soils have often been neglected when assessing fate and bioavailability of engineered nanomaterials (ENM) in soils. This review combines patchwise ENM research using natural soils with the much wider literature on ENM performed in standard tests or on the fate of colloids in soils, and an analysis of the diverse ENM characteristics determining availability from the soil organisms' perspective to assess the main soil characteristics that determine the fate, speciation, and ultimate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
206
2
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 374 publications
(229 citation statements)
references
References 204 publications
5
206
2
3
Order By: Relevance
“…As such, the concentration and bioavailability of Cu in natural environments is very important when considering ecosystem health (Flemming and Trevors, 1989). The bioavailability of Cu depends on speciation (ionic, complexed, or nano, oxidation states) and environmental factors including pH, redox potential, water, soil and sediment type, water hardness, and organic content (Garner and Keller, 2014;Flemming and Trevors, 1989;Cornelis et al, 2014). In comparison to terrestrial organisms, Cu tends to be quite toxic to aquatic biota, whose sensitivity to Cu and Cu NPs depends on factors such as surface-area-to-volume ratio, respiratory rates, and, for fish, flow rate over gill surfaces, among others (Flemming and Trevors, 1989).…”
Section: Toxicity Assessmentmentioning
confidence: 99%
“…As such, the concentration and bioavailability of Cu in natural environments is very important when considering ecosystem health (Flemming and Trevors, 1989). The bioavailability of Cu depends on speciation (ionic, complexed, or nano, oxidation states) and environmental factors including pH, redox potential, water, soil and sediment type, water hardness, and organic content (Garner and Keller, 2014;Flemming and Trevors, 1989;Cornelis et al, 2014). In comparison to terrestrial organisms, Cu tends to be quite toxic to aquatic biota, whose sensitivity to Cu and Cu NPs depends on factors such as surface-area-to-volume ratio, respiratory rates, and, for fish, flow rate over gill surfaces, among others (Flemming and Trevors, 1989).…”
Section: Toxicity Assessmentmentioning
confidence: 99%
“…Because soils and sediments appear to be major sinks for nanomaterials, these compartments must be considered in addition to pelagic aquatic compartments [50,51]. This is already reflected in the ecotoxicity tests seen for the ERA for human pharmaceuticals (Table 2).…”
Section: Ecotoxicity Testsmentioning
confidence: 99%
“…They also demonstrated that soil texture, rather than organic matter, controlled MWCNT mobility. Cornelis et al [66] reviewed the fate and bioavailability of engineered nanomaterials in soils. They concluded that some general trends can be deducted.…”
Section: Fate and Impacts Of Carbon Nanotubes On Soil And Related Orgmentioning
confidence: 99%